A study on fluctuation performance of Malaysian Servicer Exhibition (MSE): MATRADE in focus / Khairul Afidah Nordin - Nordin, Khairul Afidah (Faculty of Business and Management, 2011)
This research is conducted as a partial fulfillment of the coursework of Project Paper (IBM 662). Title of the study is “An Empirical Study on Fluctuation Performance of Malaysian Services Exhibition: MATRADE in Focus”. The main objective of the study is to assess the course of MSE inconsistency performance. MSE is an important promotional event for MATRADE in branding Malaysian services provider globally. Government allocates a huge fund to organize this event. For each edition, about RM1.2mil is injected in MATRADE fund for this program. With hope that this program will increase Malaysian trade performance and Malaysian Gross Domestic Profit (GDP) in future, Malaysian Government committed to penetrate Malaysian services industry in UAE. Including 2011, MSE is now 4 years old in organization. Within this period, the performance and achievement of MSE is quite impressive as it contribute about 1.2% of Malaysian Economic growth. Nevertheless, the performance in term of participation and sales along the years were fluctuated.